Highly sensitive electrochemical immunosensor based on methylene blue-reduced graphene oxide nanocomposites as signal probes for IL-6 detection in gingival crevicular fluid samples - Zhu, Changfeng; Wang, Hongxin; Liu, Jiyang (Frontiers in Chemistry, 2025)
As an important inflammatory cytokine, interleukin-6 (IL-6) can mediate the entire pathological process of periodontitis and is closely associated with the degree of inflammation. Therefore, it is critical to develop convenient quantitative methods for monitoring IL-6 quantity in gingival crevicular fluid. In this study, methylene blue (MB)-decorated reduced graphene oxide (rGO) is employed as signal probe to further support the antibody-enabling specific recognition of IL-6. Due to π–π stacking and electrostatic interactions, rGO-MB nanocomposites can be stably obtained. rGO with good conductivity and large surface area characteristics promotes the redox signals of MB on the glassy carbon electrode (GCE). In addition, through the simple in situ self-polymerization of dopamine, the polydopamine (PDA) obtained can be not only directly used as a biological crosslinking agent for covalent immobilization of anti-IL-6 antibody but can also be regarded as a protective layer to enhance the stability of rGO-MB on the GCE surface. Such a designed PDA/rGO-MB/GCE-based immunosensor enables specific binding with IL-6 and produces a decreased electrochemical signal for MB, realizing the selective and sensitive quantitative measurement of IL-6. Consequently, our fabricated PDA/rGO-MB/GCE-based electrochemical immunosensor has an excellent linear relationship with IL-6 ranging from 1 pg/mL to 100 ng/mL, with a limit of detection as low as 0.48 pg/mL. Moreover, our as-prepared sensing strategy shows accurate monitoring of the IL-6 quantity in gingival crevicular fluid samples.